Identification of beneficial populations for targeted-immunotherapy combinations: tailoring later-line care for patients with pMMR/MSS metastatic colorectal cancer - Li, Dan; Jin, Hui; Liu, Yan; Liu, Jiayin; Zhang, Xue; Wang, Long; Fan, Zhisong; Feng, Li; Zuo, Jing; Han, Jing; Wang, Yudong (Frontiers in Immunology, 2024)
Objective This study explores the benefits of targeted-immunotherapy combination in third-line or beyond treatment for microsatellite stable (MSS) metastatic colorectal cancer (mCRC) in a real-world setting. Methods Patients with MSS mCRC who were treated with either a targeted-immunotherapy combination or targeted therapy alone in the third-line or beyond setting at our hospital from August 2018 to August 2022 were included in the study. Inclusion criteria comprised patients treated with targeted therapy alone or in combination with immunotherapy. Effectiveness was compared between treatments, and patients with the potential to benefit from targeted-immunotherapy combination were identified. Results Among 71 patients, 31 received targeted therapies alone (TT group) and 40 received a combination of targeted therapy and immunotherapy (TI group). The TI group had higher objective response rates (20% vs 3.2%) and disease control rates (82.5% vs 58.1%). The median progression-free survival was significantly better in the TI group (4.6 vs 4.1 months, P = 0.027). Liver metastasis was associated with poor prognosis, while patients with only lung metastases had the longest median progression-free survival of 12.3 months with combination therapy. Conclusion The study indicates that targeted-immunotherapy combination offers more benefits than targeted therapy alone for MSS mCRC in the third-line or beyond setting.